Riba (Interest) as Structural Distortions: A Comparative Study of Classical Islamic Thought and Contemporary Economic Theories (Al-Qamar, 2025)
This research paper examines how interest, a seemingly benign price of credit, serves as a structural force that shapes economic outcomes across various scales. We explore the disadvantages of interest at the micro level—within households, firms, and financial institutions—and at the macro level, encompassing national budgets, international monetary systems, and global sustainability. Drawing on historical and modern theories, comparative case studies, and empirical data, we demonstrate that interest not only redistributes wealth upward but also distorts investment decisions, worsens inequality, and amplifies economic cycles. The paper contrasts conventional interest-bearing finance with non-interest risk-sharing models in Islamic finance, showing that Islamic banks exhibited greater resilience during the 2008 global financial crisis. We also document how interest‑driven incentives contribute to resource misallocation, including the destruction of food surpluses in rich countries to preserve prices. To provide a holistic perspective, we explore interdisciplinary themes, including climate change, sustainability, and ethical finance. The final section presents policy recommendations—ranging from debt restructuring and regulating predatory lending to expanding risk-sharing instruments and reforming the international financial architecture—to move toward a more equitable and sustainable economy.
Keywords: Interest, inequality, Islamic finance, debt overhang, sustainability, financial crises, public debt, food waste, risk‑sharing